The Existence of Gender Awareness on the Buginese Community in Parepare City of Indonesia - Fawziah Zahrawati; Andi Aras; Claver Nzobonimpa (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study aims to determine the problems related to the division of gender roles and the existence of gender awareness in the Buginese tribe community. The research method is qualitative with the research location in Parepare, South Sulawesi Province, Indonesia. Data got through interviews and observations. These data are collected, reduced, and presented as research findings. The findings of this study are the division of gender roles in the Buginese tribe group dealing with the problem of double burdens and stereotypes. The existence of gender awareness in the Buginese tribe community can be seen from participation in education and the economy, representation in positions in the public sphere, and the distribution of roles and responsibilities in the domestic sphere. The existence of gender awareness cannot be separated from the challenges of changing social structures that have the potential to present various problems of stability in family resilience. Therefore, this study suggests the importance of revitalizing the philosophy of life of the Buginese tribe who are pro-gender equality, such as a’bulo sibatang, sipatuo sipatokkong, and sibali perri. In addition, it is necessary to involve men in the domestic sphere to maintain family resilience and maintain the spirit of gender equality for the realization of a prosperous society.